2023
DOI: 10.1038/s42003-022-04399-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis in a model sea anemone reveals phylogenetic complexity and a role in cnidocyte discharge of DEG/ENaC ion channels

Abstract: Ion channels of the DEG/ENaC family share a similar structure but serve strikingly diverse biological functions, such as Na+ reabsorption, mechanosensing, proton-sensing, chemosensing and cell-cell communication via neuropeptides. This functional diversity raises the question of the ancient function of DEG/ENaCs. Using an extensive phylogenetic analysis across many different animal groups, we found a surprising diversity of DEG/ENaCs already in Cnidaria (corals, sea anemones, hydroids and jellyfish). Using a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 83 publications
5
17
0
Order By: Relevance
“…is completely closed at neutral pH). This includes vertebrate ASICs Coric et al 2005;Springauf & Grunder, 2010;Waldmann et al 1997b;Zhang & Canessa, 2002), likely Drosophila Ppk1 (Boiko et al 2012) (although this has not been confirmed by heterologous expression), C. elegans ASIC-1 and DEL-9 (Kaulich et al 2022b) and cnidarian, brachiopod, phoronid, annelid, xenacoelomorpha and hemichordate representatives (Aguilar-Camacho et al 2022;Martí-Solans et al 2022). The other subgroup of the acid-activated channels includes the human ENaCs (Collier & Snyder, 2009;Ji & Benos, 2004) and C. elegans ACD-2 (Kaulich et al 2022b), which show some basal activity that can be blocked by amiloride and enhanced by acidic extracellular pH.…”
Section: Acid-sensing Members Found Across Phylamentioning
confidence: 99%
“…is completely closed at neutral pH). This includes vertebrate ASICs Coric et al 2005;Springauf & Grunder, 2010;Waldmann et al 1997b;Zhang & Canessa, 2002), likely Drosophila Ppk1 (Boiko et al 2012) (although this has not been confirmed by heterologous expression), C. elegans ASIC-1 and DEL-9 (Kaulich et al 2022b) and cnidarian, brachiopod, phoronid, annelid, xenacoelomorpha and hemichordate representatives (Aguilar-Camacho et al 2022;Martí-Solans et al 2022). The other subgroup of the acid-activated channels includes the human ENaCs (Collier & Snyder, 2009;Ji & Benos, 2004) and C. elegans ACD-2 (Kaulich et al 2022b), which show some basal activity that can be blocked by amiloride and enhanced by acidic extracellular pH.…”
Section: Acid-sensing Members Found Across Phylamentioning
confidence: 99%
“…Some HyNaCs are very sensitive to their peptide ligands and start to open at low nanomolar concentrations of RFamides (Assmann et al., 2014). Although also activated by RFamide neuropeptides, HyNaCs have only a distant relationship to FaNaCs (Aguilar‐Camacho et al., 2022; Assmann et al., 2014; Golubovic et al., 2007). It is also becoming clear that W/Famides in cnidarians, including Hydra‐RFamides, are not one‐to‐one orthologues of any of the bilaterian W/F/Yamide families.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, Hydra‐RFamide III (KPHLRGRF‐NH 2 ) and Hydra‐RFamide IV (HLRGRF‐NH 2 ) do not activate HyNaCs (Golubovic et al., 2007), although they have the same C‐terminal sequence as Hydra‐RFamide I and II, suggesting that the N‐terminal part of the peptides makes important contributions to binding or activation of HyNaCs. Given that HyNaCs have a relatively close relationship to ASICs (Aguilar‐Camacho et al., 2022; Assmann et al., 2014; Golubovic et al., 2007) homology models can reveal whether they possess a cavity corresponding to the acidic pocket of ASICs. Although the acidic residues of this pocket are not conserved in HyNaCs, it would still be a candidate for the ligand binding pocket of HyNaCs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations